Social enterprise and corporate social responsibility: Toward a deeper understanding of the links and overlaps. Issue 3 (17th October 2017) - Palakshappa, Nitha; Grant, Suzanne
Abstract : Purpose: The purpose of this paper is to explore the concepts of social enterprise (SE) and corporate social responsibility (CSR). Both terms are regarded as pivotal but somewhat related when discussed in scholarship. Despite this few attempts have been made to isolate the manner in which they connect. Design/methodology/approach: In this paper the authors attempt to unpack these two terms in order to isolate key areas of overlap in their use and operationalization. In doing so, the authors address the call for work to synthesize the highly fragmented literature. Findings: The paper demonstrates that, while SE and CSR retain a unique place in the business-society landscape, there is indeed an overlap between the two. The generation of value – social, collaborative, or strategic – appears to be a central theme that connects the two concepts. Originality/value: The authors offer a detailed discussion of how SE and CSR have contributed to scholarship, and demonstrate that the two terms are indeed interrelated on many levels.